The Anisotropic Behavior of a Clay Shale: Strength, Hydro‐Mechanical Couplings and Failure Processes - Winhausen, L.; Khaledi, K.; Jalali, M.; Bretthauer, M.; Amann, F. (Journal of geophysical research. Solid earth, 2023)
Many rocks exhibit a structural composition, which leads to an anisotropic behavior of different properties. A proper understanding of the directional dependency of these properties is required to analyze and predict the failure behavior of the rock mass upon stress changes during many geo‐engineering applications. This study investigates the selected host rock for nuclear waste disposal in Switzerland, Opalinus Clay, for its anisotropic unconfined compressive and tensile strength, poromechanical response, and effective shear strength in an extensive laboratory testing campaign. The results show the lowest unconfined compressive strength at angles of 30°–45° between the bedding plane and the compressive load direction, whereby the lowest tensile strength is found to be normal to the bedding orientation. Triaxial consolidated‐undrained compression tests reveal an anisotropic poromechanical behavior as well as peak and residual effective strength values, which are largely controlled by the orientation of the bedding plane with respect to the maximum principal stress. The magnitude of excess pore water pressures and dilation are both functions of loading configuration. The comparison of peak strength values for different loading angles indicates that the lowest effective shear strength can be expected at a loading configuration of approximately 45° between bedding orientation and the loading axis. The variation in the hydro‐mechanical response is associated with the microstructure controlling the poroelasticity and the failure processes. The results provide a deeper understanding of failure in anisotropic rocks contributing to the development of constitutive models for predicting the rock mass response. Plain Language Summary The structural composition of many rocks, governed by the arrangement of grains and pores, often creates an anisotropy influencing the mechanical, hydraulic, and hydro‐mechanical properties. For different geo‐engineering applications, a proper knowledge of these properties with respect to the structural anisotropy is very important to understand and predict the response of rock masses due to changing stress conditions. The Opalinus Clay formation is the selected host rock for nuclear waste disposal in Switzerland and the subject of this study is to determine the directional dependency of elasticity, strength, poromechanical and failure behavior through a variety of experimental laboratory tests. The results show that the lowest unconfined and confined compressive shear strength is found for angles of 30°–45° between the plane of isotropy and the compressive load direction. The least stress is required for failure in tension applied normal to the anisotropy plane. In triaxial tests under undrained conditions and for different loading angles, the effective stress change during load application shows significant differences indicating different amounts of dilation which is supported by the analysis of deformation zones in the failed specimens on the microscale. Key Points Structural anisotropy causes anisotropic behavior of hydro‐mechanical response of a shale in confined and unconfined laboratory experiments Loading configuration influences elasticity, poromechanics, and failure behavior in tensile, uniaxial and triaxial compressive loading Failure causes shear strain localization by different microstructural expressions in accordance with analyses of effective stress paths